Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s42865-020-00013-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating ground-based radar and spaceborne infrared radiometer synergy for lightning areal prediction in complex orography

Abstract: A new multi-sensor approach, named PoLCast (Probability of Lightning foreCast), for predicting the lightning activity in a complex orography geographical area is proposed and discussed. The PoLCast input information are the ground-based weather radar horizontally polarized reflectivity factor and the atmospheric instability indexes, derived from the Spin Enhanced Visible Infrared Imager (SEVIRI) radiometer onboard the Meteosat Second Generation (MSG) satellite. The weather radar data are used to calculate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Several studies have proposed a hybrid system consisting of both radar and radiometer to improve the performance of the target-detecting system [10][11][12][13][14][15][16]. Some studies employed the frequency division method using a duplexer or diplexer in the radio frequency (RF) section [10,11], where the FMCW radar and radiometer share the same antenna.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have proposed a hybrid system consisting of both radar and radiometer to improve the performance of the target-detecting system [10][11][12][13][14][15][16]. Some studies employed the frequency division method using a duplexer or diplexer in the radio frequency (RF) section [10,11], where the FMCW radar and radiometer share the same antenna.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these two sensors are not time-synchronous, causing the deterioration of the detection performance, especially for timecritical missions such as the detection of targets of interest for shells and projectiles. The results of recent studies [14][15][16] demonstrated that combining the outputs of radars and radiometers mounted on satellites improved the radar detection performance. However, these works primarily involved software convergence instead of hardware convergence.…”
Section: Introductionmentioning
confidence: 99%